Аnalysis of methods of calculating road structures based by shear resistance in the soil - A. S. Aleksandrov (Вестник СибАДИ, 2021)
Introduction. Checking the soil of the subgrade and the layers of road pavement made of loosely cohesive materials by shear resistance is one of the three mandatory conditions for calculating road clothing according to strength criteria. The methodology for checking the soil of the subgrade and the sandy layers of the road pavement is constantly being modified, which is why changes concerning certain calculation details appear in each new version of the regulatory document. The purpose of this work is to analyze the advantages of the classical solution of A.M. Krivissky and to reveal the essence of the errors made in subsequent modifications of this calculation.Materials and methods. The analysis of solutions is carried out from the standpoint of compliance with the basics of mechanics. It is shown that the calculation of the total shear stress in the classical solution of A.M. Krivissky is performed in accordance with the principle of force superposition, which consists in calculating the components of the stress tensor from each force (time load and the own weight of the layer materials) separately, followed by summing the corresponding components. In this case, the active shear stresses from the temporary load and the own weight of the materials are calculated as the equivalent stress of the Mohr-Coulomb criterion. The calculation of these two components of the total shear stress is performed at the same value of the internal friction angle. Since the angle of inclination of the sliding surface to the main axes is determined by the sum or difference of 45 degrees and half of the internal friction angle, the tangential and normal stresses, which are components of the active shear stress, both from the temporary load and the own weight of the materials, are determined for the same shear surface rotated to the main axes at the same angle. In the current normative calculations, the active shear stresses from the temporary load and the own weight of the materials are determined at different angles of internal friction. This means that the active shear stresses from the temporary load and the own weight of the materials act on two different shear surface rotated to the main axes at different angles. Such stresses cannot be summed up or compared with each other. In addition to this error of the normative calculation methods, their other disadvantages are given.Results. As a result of a detailed analysis of the known modifications of the classical solution, obvious contradictions to the principles of continuum mechanics are established. As an alternative to modern calculation criteria for shear resistance, the article presents criteria for soil strength in which the shear stress exceeds the equivalent stress in the Mohr-Coulomb criterion. The principle of deducing formulas for calculating the first critical load and the total shear stress from the strength criteria under consideration is shown.Conclusion. Conclusions are drawn about the need to return to the classical solution obtained by specialists of the Leningrad School of the USSR, or to develop a fundamentally new solution based on a new plasticity condition in which the total shear stress exceeds the similar characteristic of the stress state of the original Mohr - Coulomb criterion.